PENERAPAN ENVIRONMENTAL MANAGEMENT ACCOUNTING UNTUK MENCAPAIECO-EFFICIENCY PADA PT. INDO BALI DI BALI - Dea Kriseta Paramastri; Wiyono Pontjoharyo (CALYPTRA, 2018)
Abstract - The purpose of the study in general is to seek a more efficient EMA by using the concept of eco-efficiency. This research is expected to analyze in detail the existing EMA at PT. Indo Bali and looking for solutions to the company's environmental management system to be better, so this research is classified as explanatory research. This type of research is applied research, because this research is done to apply EMA to achieve eco-efficiency in PT.Indo Bali. The result of the research is that there is no record of environmental cost related to the business entity, so it can not be known whether the production process has been efficient. By using EMA, it is expected that business entity can achieve eco-efficiency so that the performance of business entity becomes maximal.